Soil organic carbon stocks in topsoil and subsoil controlled by parent material, carbon input in the rhizosphere, and microbial-derived compounds. (July 2018) - Angst, Gerrit; Messinger, Johanna; Greiner, Maria; Häusler, Werner; Hertel, Dietrich; Kirfel, Kristina; Kögel-Knabner, Ingrid; Leuschner, Christoph; Rethemeyer, Janet; Mueller, Carsten W.
Abstract: Despite a large body of studies investigating soil organic carbon (SOC) stocks and potential influencing factors, the impact of contrasting parent material, particularly in the subsoil, has received little attention. To reveal potential effects varying parent materials exert on SOC stocks, we investigated chemical ( 14 C content and overall chemical composition via 13 C NMR spectroscopy) and plant/microbial related parameters (root mass, amino sugars) of bulk soil and soil organic matter fractions from topsoil, subsoil, and rhizosphere soil at three European beech stands ( Fagus sylvatica L.) only differing in parent material (Tertiary sand, Quaternary loess, and Tertiary basalt). The results suggest that the clay fraction, its amount being largely dependent on the respective parent material, took a central role in shaping differences in SOC stocks among the investigated sites by affecting soil organic matter stabilization via organo-mineral association and aggregation. This fraction was particularly relevant in the subsoil, where it accounted for up to 80% of the bulk soil SOC stocks that decreased with decreasing amounts of the clay fraction (basalt > loess > sand site). Determining the soil's nutrient composition, parent material likely also indirectly affected SOC stocks by changing rhizosphere traits (such as fine root density or mortality) and by attracting root growth (and thus organic matter inputs) to subsoil with higher nutrient contents, where in situ root inputs in the form of rhizodeposits were likely the prime source of plant-derived SOC. However, root inputs also contributed in large part to topsoil SOC stocks and were associated with higher abundance of microbial compounds (amino sugars), whose relative importance increased with increasing soil depth. Independent of soil depth and site, amino sugars and the amount of the clay fraction, combined with parameters related to the input of organic matter (root mass and amount of the particulate organic matter fraction) explained more than 90% of the variability in SOC stocks, indicating a key role of these measures in impacting SOC stocks. Because parent material directly or indirectly influenced these parameters, we demonstrate the necessity to consider differences in parent material when estimating and predicting SOC stocks. Graphical abstract: Image 1 Highlights: The clay fraction, particularly in the subsoil, shaped differences in SOC stocks. In the topsoil, the relevance of the clay fraction was attenuated by root inputs. Microbial residues were constant or slightly increased with soil depth. Amino sugars, root mass, clay and POM explained ∼90% of variation in SOC stocks.